PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU (Studi Pada SMK 17 Agustus 1945 Semarang) - Fania Puspa Andiani, 13.05.51.0097 (Students' Journal of Economic and Management, 2017)
This study examines and analyzes the influence of motivation, work discipline and work environment on teacher performance. This research was conducted at SMK 17 August 1945 Semarang. The population of this study is all teachers of SMK 17 August 1945 Semarang which amounted to 52 people by taking sempel using census method. The method of analysis used in this study is to use regression analysis method, that is using the value of Standardized Coefficients Beta and significant level. The result of the research shows that motivation has positive and significant effect to teacher performance, work discipline has positive and significant influence to teacher performance, and work environment have positive and significant effect to teacher performance. Keywords: Motivation, Work Discipline, Work Environment and Teacher Performance.